Bulakeña : anyo at kasaysayan ng baro't saya - Enriquez, Milagros S., 1923- 4 0 16; 5 (Malolos, Bulacan : Center for Bulacan Studies, 1999)
History of traditional attire of Bulacan Province, Philippines.
Includes bibliographical references (p. 103).
In Tagalog.
Keywords: 2 -- 0; 6; 20; 20; 2